Rigler's triad in gallstone ileus: a case report - Sergio, Jacobo F.; Y., Santacruz A. Sara; Erick, Hidrogo O.; Rogelio, Romero V.; Vicente, García C. Salvador; Gael, Ramírez V.; Guillermo, Gonzalez C.; Sigifredo, Garcia R. (International Journal of Research in Medical Sciences, 2024)
Gallstone ileus, a rare complication of cholelithiasis. This condition occurs when a large gallstone causes mechanical obstruction within the gastrointestinal (GI) tract, often due to a fistula between the gallbladder and the duodenum or stomach. Bouveret syndrome, a subset of gallstone ileus, involves gastric outlet obstruction caused by a gallstone. Here, we present the case of a 61-year-old female admitted with acute biliary pancreatitis, later diagnosed with gallstone ileus. Imaging revealed Rigler’s triad, and surgical intervention included an exploratory laparotomy, enterolithotomy, and staged management of a cholecystoenteric fistula. Despite successful surgery, the patient’s follow-up was limited due to voluntary discharge. This case highlights the complexity of gallstone ileus management and underscores the challenges in determining the optimal surgical approach, particularly in transient patient populations.